If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -10) = 5(x + -8) Reorder the terms: 2(-10 + x) = 5(x + -8) (-10 * 2 + x * 2) = 5(x + -8) (-20 + 2x) = 5(x + -8) Reorder the terms: -20 + 2x = 5(-8 + x) -20 + 2x = (-8 * 5 + x * 5) -20 + 2x = (-40 + 5x) Solving -20 + 2x = -40 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -20 + 2x + -5x = -40 + 5x + -5x Combine like terms: 2x + -5x = -3x -20 + -3x = -40 + 5x + -5x Combine like terms: 5x + -5x = 0 -20 + -3x = -40 + 0 -20 + -3x = -40 Add '20' to each side of the equation. -20 + 20 + -3x = -40 + 20 Combine like terms: -20 + 20 = 0 0 + -3x = -40 + 20 -3x = -40 + 20 Combine like terms: -40 + 20 = -20 -3x = -20 Divide each side by '-3'. x = 6.666666667 Simplifying x = 6.666666667
| 1=3r-4 | | (4x-10)(24+5x)=0 | | 8=6+3p | | 0=4m-5 | | -136-8x=-102-10x | | 15(4a-3)+37a=42-111 | | 18+3h=22 | | 4(6x+3)+9(3x-5)=324 | | 9x+2-7x+6=9x-7x+5 | | (7x-6)(x-5)=(x+3)(1-2x) | | 8x-17=5-3x | | 3x+8=2x+17 | | -168-3x=16x+12 | | 12x+4=-31-3x | | 3x(-x-2)=0 | | 7w+5=5 | | 124-12x=11x+16 | | 2x^2+32x+a=0 | | -14-5x=7-2x | | 103-3x=17x+19 | | 67-7x=2x+15 | | 10d+3e-5d-e= | | 11x=90-1x | | -5x+3=13 | | x+3x=5 | | e^2x=1 | | 7x-4=3x+23 | | 6a+86=13a-5 | | y=x^2+10+12 | | 36-2x=7x+21 | | e^0.01t=e^0.02t-1/5 | | 7-10x=59-38x |